Investigation of the price linkage between Asian LNG spot and Far East Asian LNG prices and its implications - Pradipta, Muhammad Anas (Purnomo Yusgiantoro Center, 2018)
For so many times, Far East Asian liquid natural gas (LNG) buyers have been using price linked to crude oil-indexed, now they need to find another alternative pricing formula for their crucial energy supply as a better price structure that could reflect the market is needed. LNG spot price is expected to be the pillar for the future LNG trading, especially for Far East Asia Market. As less and less long-term contracts are signed in the Far East Asia Market, this creates an additional demand for the LNG in the spot market, while it raises some issues about the presence of different LNG pricing mechanisms. Most of the LNG spot prices in Asia are indexed to the relatively low natural gas prices in Atlantic Basin. Furthermore, the advancement of drilling technology in the US drives down its natural gas prices, resulting in price discrepancies between Asian LNG spot and East Asian LNG prices. This study investigates whether there is a price linkage between Asian LNG spot and East Asian LNG prices. This study comprehends 91 observations collected from January 2010 to July 2017. Johansen co-integration tests were carried out to examine the existence of long-run relationship on the spot, Japanese and South Korean LNG prices. The Augmented Dickey-Fuller (ADF), Phillip-Perron (PP), and Kwiatkowski-Phillips-Schmidt-Shin (KPSS) unit root tests were conducted first before proceeding to the co-integration tests. The results showed that Asian LNG spot prices did not have price linkage for monthly averages of Japanese and South Korean LNG prices. The analyses also indicated that Taiwan LNG markets move together with Asian LNG spot markets. As a conclusion, the results inferred that supply dependency on LNG spot cargoes governed the price linkage among these Asian LNG markets. The use of gas indexed LNG price mechanism did not reflect the economic fundamentals in Asia-Pacific Basin. JEL Classification: Q41